Concentrations of PM0.1 and PM2.5 at high polluting event days in Ha Noi and the effects of meteorological conditions - Vo Thi Le Ha,; Van Dieu Anh,; Nguyen Thi Thu Hien,; Dao Duy Nam,; Nghiem Trung Dung,; Ly Thuy Bich, (Vietnam Journal of Science and Technology, 2023)
. High levels of fine (PM2.5) and ultrafine (PM0.1) particles in the atmosphere can cause adverse effects on the environment and human health. This study aims at determining the mass concentrations of PM and meteorological influencing factors in high pollution event days in Hanoi. Daily samples of PM2.5 and PM0.1 were collected at a mixed site in Hanoi, Vietnam, from the middle of October to December 2020. High pollution events were determined based on PM2.5 concentrations and analyzed for its average concentration and intensity (number of days). The regression analysis and correlation matrix were determined by R software, version 4.04. Seven high pollution events were recorded for 2.5 sampling months. The daily PM2.5 concentrations were in the range of 19 - 147 µg/m3. Those of PM0.1 varied from 2 to 13 µg/m3 with an average of 6 µg/m3. The investigated meteorological factors can explain 70% PM2.5 variation but only 47% of PM0.1 variations.